Existential/Humanistic theory in practice - Hutchinson, David; Houghton Mifflin Co.; Lahaska Press ([Framingham, MA.] : Distributed by Microtraining Associates, 2004)
This video shows three counseling session with a counselor, Davis Hutchinson. Also includes the discussion sessions
Title from title screen
Executive producer, Mary Falson
Host: Susan X. Day
Counselor: David Hutchinson
Keywords: Humanistic counseling; Humanistic psychotherapy; Existential psychotherapy; Counseling